PENINGKATAN PENGETAHUAN MELALUI SOSIALISASI EMPAT PILAR KEBANGSAAN PADA PELAJAR DI SEKOLAH MENENGAH DAN KEJURUAN (STUDI PADA SMAN 2 DAN SMKN 3 KOTA BENGKULU) - Ika Pasca Himawati; Heni Nopianti (DHARMA RAFLESIA, 2018)
Indonesia has culture diversity considered as national asset. But, if culture diversity is not managed well, it will trigger gap, conflict, disunity and violence. Therefore, the attempt to reconstruct four nationality pillars is essential. The goal is to give concept of be-Indonesian as integrative, comprehensive, and also become the foundation to enhance national unity. Four nationality pillars are: Pancasila as national ideology, basic law of 1945 as national constitution, Negara Kesatuan Republik Indonesia (NKRI) as the form of the country and Bhinneka Tunggal Ika as the national motto. The target of this program is students in 3 senior high schools and vocational high school in Bengkulu city. The methods in community service activities are workshops through the provision of material which begins with pre-test activities and ends with post test, FGD, and mentoring. After the activity, the knowledge of the students about the four nationality pillars has increased significantly. From the activities conducted in 2 schools, it is found that the average increase of students' knowledge about the four pillars of nationality increased up to 30.8% and 38.7%. Each school always disseminates knowledge about the four nationality pillars through teaching in each school. The distribution of knowledge about the four nationality pillars is not only done among students, but also for the teachers. The goal is to be able to reconstruct and internalize the four nationality pillars as an effort to strengthen the soul of nationalism and minimize acts of violence that can be a potential for radicalism and national division.  Keywords: Four Nationality Pillars, Nationalism, Student